Mobile device ownership among emergency department patients. (June 2019) - Kim, Eugene; Torous, John; Horng, Steven; Grossestreuer, Anne V.; Rodriguez, Jorge; Lee, Terrance; Nathanson, Larry A.
Highlights: Mobile device ownership is high among Emergency Department patients. Patients are interested in using mobile devices for many aspects of medical care. Older patients and those without commercial insurance own fewer smartphones. Patients have concerns about privacy when using mobile applications. Abstract: Background: The landscape of mobile devices is changing and their present use by patients for healthcare purposes is unknown. An understanding of current attitudes and usage may help increase patient engagement through mobile applications. This study sought to determine characteristics of mobile device ownership among Emergency Department patients, patients' feelings regarding their use in healthcare, and desired functionality in mobile applications. Methods: A cross-sectional survey was undertaken at a single urban tertiary care academic center. A convenience sample of adult English-speaking patients in the Emergency Department were surveyed from June 21 st, 2017 to December 30th, 2017. A secondary analysis of the data was performed based on demographic and socioeconomic factors. Results: 260 patients were approached for participation, 11 patients declined, and one patient was excluded. The 248 participants had a median age of 49 (interquartile range 28–62) and 54% were female. 91% of those surveyed own smartphones, 58% owned tablets, and 77% of these patients were comfortable using mobile devices. Those without mobile devices were older (p < 0.001) and held less commercial insurance (p = 0.01). A majority of patients were interested in using applications to enter information, track their visit, view results, and communicate with providers during their visit. Following care, there is interest in viewing information about their visit and receiving reminders for appointments and medications. Patients are also interested in using applications for learning about medical conditions and managing medications. Though there are mixed feelings regarding the protection of privacy by apps, they are felt to be safe, effective, useful, and not difficult to use. Conclusion: Ownership of smartphones is high across the Emergency Department population and patients are enthusiastic about using mobile devices as part of their care. Further study can elucidate opportunities to further integrate mobile device applications into patient care.